"Modified Dynamic Needle Tip Positioning" Short-Axis, Out-of-Plane, Ultrasound-Guided Radial Artery Cannulation in Neonates: A Randomized Controlled Trial. (July 2019) - Liu, Lifei; Tan, Yanzhe; Li, Shangyingying; Tian, Jie
Abstract : BACKGROUND: Radial artery cannulation is extremely challenging in neonatal patients. Herein, we compared the success rate of the modified dynamic needle tip positioning short-axis, out-of-plane, ultrasound-guided technique with that of the traditional palpation technique in neonatal radial artery cannulation. METHODS: Sixty term neonates undergoing major abdominal surgery were randomized into the ultrasound or palpation group via the sealed-envelope method. The ultrasound group underwent radial artery cannulation using an ultrasonic apparatus, while traditional palpation of arterial pulsation was used in the palpation group. The arterial diameter and depth were measured on ultrasound before the puncture. We recorded age, weight, sex, and other background characteristics. The primary outcomes included the first-attempt, total success rates, and the total puncture procedure duration. Secondary outcomes included the incidence of complications (hematoma and thrombosis). Data were compared between the 2 groups. RESULTS: Sixty term neonates were enrolled in the study. The success rates of the first attempt in the ultrasound and palpation groups were 40% (n = 30) and 10% (n = 30), respectively ( P = .007; relative risk, 4.0; 95% confidence interval, 1.3–12.8). The total success rate was 96.7% in the ultrasound group and 60.0% in the palpation group ( P = .001; relative risk, 1.61; 95% confidence interval, 1.19–2.17). The average time to accomplish radial artery cannulation in the ultrasound and palpation groups was 91.4 ± 55.4 and 284.7 ± 153.6 seconds, respectively ( P < .001; estimated difference, −193; 95% confidence interval, −256 to −130). In addition, 3.3% of the patients in the ultrasound group and 26.7% in the palpation group suffered puncture hematoma ( P = .026; relative risk, 0.13; 95% confidence interval, 0.02–0.94). CONCLUSIONS: Modified dynamic needle tip positioning short-axis, out-of-plane, ultrasound-guided radial artery cannulation in neonates improves the first-attempt and total success rates and decreases the total procedural time and incidence of cannulation-related complications.